STUDY PARAMETERS DEFINING EFFICIENCY IN REMOVAL OF CONSTRUCTION WORKS STRUCTURES - and and (Municipal economy of cities. Series: «Economy science», 2013)
In the article the indications determining efficiency of dismantling of a building unit are investigated. The attention is paid to the main defects of buildings and structures including the results of man-caused emergencies. Principal indications demonstrate constrained space on the building site where dismantling takes place.